Effects of therapeutic hypothermia on the gut microbiota and metabolome of infants suffering hypoxic-ischemic encephalopathy at birth. (December 2017) - Watkins, C.; Murphy, K.; Yen, S.; Carafa, I.; Dempsey, E.M.; O'Shea, C.A.; Vercoe, E.A.; Ross, R.P.; Stanton, C.; Ryan, C.A.
Abstract: Neonatal hypoxic ischemic encephalopathy (HIE) in the perinatal period can lead to significant neurological deficits in later life. Total body cooling (TBC) is a neuroprotective strategy used in the treatment of HIE and has been shown to reduce seizures and improve neurodevelopmental outcomes in treated infants. Little is known, however, about the effects of HIE/TBC on the developing gut microbiota composition and subsequent metabolic profile. Ten term infants with HIE who received TBC at 33.5 °C for 72 h were recruited. A control group consisted of nine healthy full term infants. Faecal samples were collected from both groups at 2 years of age and stored at −20 °C. 16S rRNA amplicon Illumina sequencing was carried out to determine gut microbiota composition and 1H NMR analysis was performed to determine the metabolic profile of faecal water. The gut microbiota composition of the HIE/TBC infants were found to have significantly lower proportions of Bacteroides compared to the non-cooled healthy control group. Alpha diversity measures detected significantly lower diversity in microbial richness in the HIE/TBC infant group compared to the control infants (Shannon index, <0.05). High inter-individual variation was found in gut microbiota composition and metabolic profile of both groups. Initial principal coordinate analysis and hierarchal clustering of compounds on MetaboAnalyst 3.0 indicated no clear separation in the metabolic profile of these two infant groups. These results suggest that there is no significant impact on the gut microbial development of HIE/TBC infants compared to healthy infants at 2 years of life. To our knowledge this is the first study to report the gut microbiota composition and metabolic profile of infants who have experienced HIE/TBC at birth.